Daniel X. Game over - Patterson, James, 1947-; Rust, Ned (Patterson, James, 1947- Daniel X novels., 2012)
In Tokyo, fifteen-year-old Daniel X faces two of the most dangerous aliens on the planet, who are plotting to use video games to control children and turn them into an army of doom.